Novel benzo[b]xanthene derivatives: Bismuth(III) triflate-catalyzed one-pot synthesis, characterization, and acetylcholinesterase, glutathione S-transferase, and butyrylcholinesterase inhibitory properties - Turhan, Kadir; Pektas, Begum; Turkan, Fikret; Tugcu, Fatma T.; Turgut, Zuhal; Taslimi, Parham; Karaman, Halide S.; Gulcin, Ilhami (WILEY-V C H VERLAG GMBH, 2020)
In this study, 3,4-dihydro-12-aryl-1H-benzo[b]xanthene-1,6,11-(2H,12H)trione compounds were obtained through one-pot condensation of various substituted aromatic aldehydes, 2-hydroxy-1,4-naphthoquinone, and dimedone in the presence of Bi(OTf)(3) as a green and reusable catalyst. The structural characterization of these novel substituted benzo[b]xanthenes was performed by spectroscopic methods, and their inhibitory actions against butyrylcholinesterase (BChE), acetylcholinesterase (AChE), and glutathione S-transferase (GST) were investigated. GST is an enzyme responsible for removing toxic molecules during Phase II reactions in the detoxification mechanism. The AChE and BChE enzymes, which are called cholinesterases, are among the enzymes that occur especially during dementia such as brain damage or Alzheimer's disease. Inhibition effects of the benzo[b]xanthene derivatives on AChE, BChE, and GST were found at the millimolar level. The best inhibitor for GST is compound 4a (31.18 +/- 6.13 mM), for AChE, it is compound 4d (28.16 +/- 3.46 mM), and for BChE, it is compound 4f (36.24 +/- 3.19 mM). Compound 4a inhibited the dimerization of GST subunits, and compounds 4d and 4f directly inhibited the catalytic activity by interacting with the catalytic active site or a related site of the AChE and BChE enzymes, respectively.
Keywords: acetylcholinesterase; enzyme inhibition; molecular docking; spectrophotometry; synthesis; EFFICIENT CATALYST; REUSABLE CATALYST; 3-COMPONENT SYNTHESIS; XANTHENE DERIVATIVES; HIGHLY EFFICIENT; HYDROGEN SULFATE; SOLVENT-FREE; BENZOXANTHENES; GREEN; WATER; Pharmacology & Pharmacy; Chemistry